2009
DOI: 10.3382/ps.2009-00119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citric acid, avilamycin, and their combination on the performance, tibia ash, and immune status of broilers

Abstract: The aim of this study was to determine the effect of the supplementation of an organic acid (citric acid), antibiotic growth promoter (avilamycin), and their combination for a period of 35 d on the growth, feed efficiency, carcass yield, tibia ash, and immune status of broilers. One hundred sixty 1-d-old broiler chicks (Hubbard Classic) were randomly distributed into 4 groups with 4 replicate cages having 10 birds in each. A corn-soybean-based diet was used as the basal diet (control). The basal diet was suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
86
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 22 publications
21
86
2
9
Order By: Relevance
“…The higher carcass yield enables to infer that the antibiotic promoted reduced sanitary challenges for these broilers, which is reflected in the higher performance and yield. This result corroborates the results of Samanta et al (2008) and Chowdhury et al (2009), who evaluated the use of acidifiers in broiler diets.…”
Section: Resultssupporting
confidence: 91%
“…The higher carcass yield enables to infer that the antibiotic promoted reduced sanitary challenges for these broilers, which is reflected in the higher performance and yield. This result corroborates the results of Samanta et al (2008) and Chowdhury et al (2009), who evaluated the use of acidifiers in broiler diets.…”
Section: Resultssupporting
confidence: 91%
“…In another previous experiment, Abbas (2010) reported that organ weights and carcass characteristics were not affected by supplementing diet with 3 g kg −1 basil seed. This result is in agreement with the results of Ceylan and Ciftci (2003), Chowdhury et al (2009) and Eseceli et al (2010), who reported that there was no significant effect on carcass weight in broiler chicks fed a diet supplemented with avilamycin. Similarly, Saleh (2014) reported that supplementation with avilamycin did not significantly affect the liver weight of broilers.…”
Section: Carcass Traitssupporting
confidence: 93%
“…The diet with organic acid resulted in worse FCR (p<0.05) compared with the control treatment. On the other hand, Viola & Vieira (2007), and Chowdhury et al (2009) reported better FCR in broilers fed organic acids relative to the control diet between one and 35 days of age.…”
Section: Resultsmentioning
confidence: 87%